2016
DOI: 10.1163/22134522-12340066
|View full text |Cite
|
Sign up to set email alerts
|

Human and Deltaic Environments in Northern Egypt in Late Antiquity

Abstract: This paper analyses the relationship between archaeological sites from the Roman-Late Roman period in the north-central Delta of Egypt and the palaeotopography and environmental conditions from the 1st millennium BC to 1st millennium AD. The location of the archaeological sites is mapped according to survey maps of the 19th and 20th c. and digital topographic models from satellite data. The Ptolemaic and Roman context for the apparent ‘boom’ in settlement during the late antique period (3rd–7th c. AD) is descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Because this study is focused on detecting ancient occupations, these remote sensing indices served as a proxy to measure the differences in the vegetation value between the original marshland and barren area in the study area. By using combinations of the relevant indices (EVI2, GNDVI, OSAVI, and GEMI), we were able to take advantage of recent methodological enhancements in land use mapping [77]. The results of the remote sensing indices showed that the marshlands identified correlated significantly with the historic topographic maps.…”
Section: Discussionmentioning
confidence: 99%
“…Because this study is focused on detecting ancient occupations, these remote sensing indices served as a proxy to measure the differences in the vegetation value between the original marshland and barren area in the study area. By using combinations of the relevant indices (EVI2, GNDVI, OSAVI, and GEMI), we were able to take advantage of recent methodological enhancements in land use mapping [77]. The results of the remote sensing indices showed that the marshlands identified correlated significantly with the historic topographic maps.…”
Section: Discussionmentioning
confidence: 99%
“…Herodotus the Greek writer, geographer and historian refers to the northern part of the Delta as a marsh region (Attiah, 2011). The region was most active from the Roman through to the medieval periods (Wilson, 2012) with at least 40 town-sites and around 150 potential ancient archaeological sites identified in the area north of ancient Buto by the Egypt Exploration Society's Delta Survey Project (Egypt Exploration Society, n.d., https://www.ees.ac.uk/ delta-survey; Wilson, 2016). The geomorphology of the present coast of the Nile Delta was shaped by two tidal processes, the currents of the Mediterranean Sea and the alluvial filling of the Delta by the branches of the Nile (Torab & Azab, 2007).…”
Section: The Study Area and Historical Backgroundmentioning
confidence: 99%
“…No distinct remains of an ancient settlement have yet been discovered on the surface of, or close to, this feature, nor is there any information in the SoE maps of the CORONA or Sentinel-2 imagery. However, related work reports Ptolemaic and Roman pottery and other vestiges are found on a number of elevated sectors examined in this general eastern Burullus lagoon area [34,35]. The possibility of discovering an once-existing settlement in the vicinity of S- However, related work reports Ptolemaic and Roman pottery and other vestiges are found on a number of elevated sectors examined in this general eastern Burullus lagoon area [34,35].…”
Section: Satellite Imagery Topographic Maps and Hydrographic Modelingmentioning
confidence: 99%
“…However, related work reports Ptolemaic and Roman pottery and other vestiges are found on a number of elevated sectors examined in this general eastern Burullus lagoon area [34,35]. The possibility of discovering an once-existing settlement in the vicinity of S- However, related work reports Ptolemaic and Roman pottery and other vestiges are found on a number of elevated sectors examined in this general eastern Burullus lagoon area [34,35]. The possibility of discovering an once-existing settlement in the vicinity of S-44 is thus not excluded until more closely spaced exploratory deep drilling and archaeological subsurface surveys and excavations are made in close proximity to the study site.…”
Section: Satellite Imagery Topographic Maps and Hydrographic Modelingmentioning
confidence: 99%
See 1 more Smart Citation